Personality Type D, Level of Perceived Stress, Insomnia, and Depression Among High School Teachers in Poland - Domagalska, Joanna; Rusin, Monika; Razzaghi, Mehdi; Nowak, Przemysław (Frontiers in Psychology, 2021)
Teaching is inherently connected with specific burdens that may imply stressful situations. Psychological predispositions of the surveyed group, including personality type D (distressed personality) and level of experienced stress can cause depressive episodes and sleep disorders, which have a direct impact not only on health in terms of disease, but also on well-being and the ability to effectively and properly teach. The research group consisted of 412 high school teachers from the Silesian Province, located in the south of Poland. Using the following research tools: Type D Scale (DS14), Perceived Stress Scale (PSS-10), Athens Insomnia Scale (AIS) and Beck Depression Inventory (BDI), it was found that Type D personality was observed in a much larger percentage of teachers (30.1%) compared to normalization tests conducted in the Polish general population (about 20%). It was reported that teachers with distressed personality suffered from insomnia and depression significantly more often. Findings from the current study indicate the need to implement preventive activities focused on reducing psychosocial risk factors in the work environment in order to reduce the frequency of depressive disorders among teachers.